Postharvest Treatment with Abscisic Acid Alleviates Chilling Injury in Zucchini Fruit by Regulating Phenolic Metabolism and Non-Enzymatic Antioxidant System - Alejandro Castro-Cegrí; Sandra Sierra; Laura Hidalgo-Santiago; Adelaida Esteban-Muñoz; Manuel Jamilena; Dolores Garrido; Francisco Palma (MDPI AG, 2023)
Reports show that phytohormone abscisic acid (ABA) is involved in reducing zucchini postharvest chilling injury. During the storage of harvested fruit at low temperatures, chilling injury symptoms were associated with cell damage through the production of reactive oxygen species. In this work, we have studied the importance of different non-enzymatic antioxidants on tolerance to cold stress in zucchini fruit treated with ABA. The application of ABA increases the antioxidant capacity of zucchini fruit during storage through the accumulation of ascorbate, carotenoids and polyphenolic compounds. The quantification of specific phenols was performed by UPLC/MS-MS, observing that exogenous ABA mainly activated the production of flavonoids. The rise in all these non-enzymatic antioxidants due to ABA correlates with a reduction in oxidative stress in treated fruit during cold stress. The results showed that the ABA mainly induces antioxidant metabolism during the first day of exposure to low temperatures, and this response is key to avoiding the occurrence of chilling injury. This work suggests an important protective role of non-enzymatic antioxidants and polyphenolic metabolism in the prevention of chilling injury in zucchini fruit.